Answer:
a) [tex] f(2)= 0.448 (2)^{1.21}= 1.036 grams[/tex]
b) [tex] 0.5 = 0.448 x^{1.21}[/tex]
Dividing both sides by 0.448 we got:
[tex]\frac{0.5}{0.448} = x^{1.21}[/tex]
We can appy the exponent [tex]\frac{1}{1.21}[/tex] in both sides of the equation and we got:
[tex] (\frac{0.5}{0.448})^{\frac{1}{1.21}} = x= 1.095grams[/tex]
Step-by-step explanation:
For this case we know the following function:
[tex] f(x) = 0.448 x^{1.21}[/tex]
The notation is: x is the weight of the crab in grams, and the output f(x) is the weight of the claws in grams.
Part a
For this case we just need to replace x = 2 gram in the function and we got:
[tex] f(2)= 0.448 (2)^{1.21}= 1.036 grams[/tex]
Part b
For this case we know tha value for [tex] f(x) =0.5[/tex] and we want to find the value of x who satisfy this condition:
[tex] 0.5 = 0.448 x^{1.21}[/tex]
Dividing both sides by 0.448 we got:
[tex]\frac{0.5}{0.448} = x^{1.21}[/tex]
We can appy the exponent [tex]\frac{1}{1.21}[/tex] in both sides of the equation and we got:
[tex] (\frac{0.5}{0.448})^{\frac{1}{1.21}} = x= 1.095grams[/tex]